Treatment of Long Femoropopliteal Lesions With Self-Expanding Interwoven Nitinol Stent: 24 Month Outcomes of the STELLA-SUPERA Trial. (February 2023) - Nasr, Bahaa; Gouailler, Flora; Marret, Olivier; Guillou, Marie; Chaillou, Philippe; Guyomarc'h, Béatrice; Maurel, Blandine; Gouëffic, Yann
Purpose: The performance of self-expanding interwoven nitinol stent (Supera) in femoropopliteal interventions has been proven through trials with short lesions and with relatively low proportion of occlusions. There is limited evidence of Supera stent in long lesions. The aim of this study was to assess the clinical safety and efficiency of the Supera stent in the treatment of long femoropopliteal lesions (Trans-Atlantic Inter-Society Consensus [TASC] C/D) in patients with symptomatic peripheral arterial disease (PAD). Methods: The STELLA SUPERA (STEnting Long de L'Artère fémorale superficielle par le stent métallique Supera) is a prospective, 2-center, single-arm study. Patients with symptomatic (Rutherford stages 2–6) de novo and TASC C/D lesions of the femoropopliteal segment were treated with Supera stent. The primary endpoint was the primary sustained clinical improvement at 12 months. Follow-up included clinical examination, duplex scan, and biplane X-ray up to 24 months. Results: Between December 2016 and October 2018, 48 symptomatic patients with 49 femoropopliteal lesions (TASC D = 32, 65%) were treated. The mean lesion length was 234 ± 123 mm, and 78% were total occlusion. The mean stented lesion length was 273 ± 127 mm. At 12 and 24 months, the primary sustained clinical improvement rate was 87.2% and 79.7%, respectively. The Rutherford category assessment was significantly improved at 24 months compared with baseline (p=0.02). At 24 months, the primary patency and freedom from target lesion revascularization (TLR) rates were 77.9% and 86.9%, respectively. The ankle-brachial pressure index increased from 0.62 ± 0.15 at baseline to 0.93 ± 0.15 at 24 months (p<0.0001). There were no stent fractures at 24 months. Conclusion: The use of Supera stent in long lesions (TASC C/D) is a safe and effective endovascular alternative. These results reinforce the need for randomized clinical trials to assess the value of interwoven stents for long femoropopliteal lesions.